La maternité suisse d’Elne (Pyrénées-Orientales) 1939-1944 - Michèle François (In Situ)
This château was built for an industrialist in 1900 and, from 1939 to 1944, served as a maternity hospital for women interned in the camps at Argelès, Rivesaltes, Saint-Cyprien and Gurs. Thanks to the courage and determination of a young woman from the Swiss Red Cross, Elisabeth Eidenbenz, some 600 children and their mothers were saved from the camps, up until the closure of the hospital, by the Germans, in 1944. The children were those of Spanish Republican refugees, Jews and Gypsies. For more than fifty years, this story was forgotten and the château gradually fell into ruin before being restored by a new owner. With the help of Guy Eckstein, who was born in the maternity hospital, this new owner undertook a study of the place’s memory, which ended up with the château being given to the town of Elne, in 2005, in order to create a museum. The building was given historic monument protection on 4 March 2014.